Plataformas de aquisição de dados planialtimétricos para criação de projetos de suavização do terreno para cultivo de soja em terras baixas - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Rice cultivation is traditional in the western border, with the region being the largest contributor to national production. Over the years, other crops have been implemented in rotation with irrigated rice. Among these, soybeans have experienced the most significant expansion, cultivated with surface irrigation. This study aims to compare different platforms for collecting planimetric-altimetric data for use in terrain smoothing projects for soybean irrigation in lowlands. The work was carried out in a commercial plantation near the city of Alegrete-RS. The study involved three methodologies: 1) data collection using a low-autonomy drone, without post-processed positioning correction (PPK), with control and verification points, denominated as PC; 2) data collection using a high-autonomy drone, Nuvem Spectral 2 model, with post-processed positioning correction (PPK), without control and verification points; 3) data collection using Real-Time Kinematic (RTK) system embedded in a motor vehicle, denominated as RTK. Pre-processing of images was performed, excluding those with high drag levels using Quantum GIS®, and points that were not recorded for elevation. With the obtained Digital Elevation Models (DEMs), a dense mesh spaced by 5 meters was generated, allowing the extraction of elevation information. After obtaining the data, a box plot graph was created, resulting in two response variables, elevation and slope. Pearson correlation analysis was performed, and earth movement was estimated through a theoretical DEM using the average elevations to create a parameter. In conclusion, the proposed objectives revealed that both altimetric data collection with RTK and drones showed satisfactory planimetric-altimetric similarity in digital elevation models. When comparing earth movement estimates, consistency was observed in the PPK and RTK methodologies, with a significant discrepancy in the PC methodology, showing a variation of about 15%, making the use of drones without PPK correction unfeasible. These conclusions underscore the importance of a careful choice of methodology, considering coherence in results, operational efficiency, and possible variations in soil movement estimates. Key-words: Systematization; altimetry; RTK system; VANT.
Keywords: Engenharia agrícola; Soja; Sistematização; Altimetria; Agricultural engineering; Soybean; Systematization; Altimetry; CNPQ::CIENCIAS AGRARIAS